1999
DOI: 10.1162/089892999563265
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Processing during the Conscious Resting State: A Functional MRI Study

Abstract: Localized, task-induced decreases in cerebral blood flow are a frequent finding in functional brain imaging research but remain poorly understood. One account of these phenomena postulates processes ongoing during conscious, resting states that are interrupted or inhibited by task performance. Psychological evidence suggests that conscious humans are engaged almost continuously in adaptive processes involving semantic knowledge retrieval, representation in awareness, and directed manipulation of represented kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

79
765
4
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,009 publications
(854 citation statements)
references
References 67 publications
79
765
4
6
Order By: Relevance
“…Our object-naming meta-analysis confirmed this prediction, but also revealed areas where activation was observed more when the baseline was high than when it was low. Although this reverse effect was less expected, it is consistent with the findings of Binder et al [1999], who demonstrated that resting baselines activate areas associated with semantic relative to phonological tasks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our object-naming meta-analysis confirmed this prediction, but also revealed areas where activation was observed more when the baseline was high than when it was low. Although this reverse effect was less expected, it is consistent with the findings of Binder et al [1999], who demonstrated that resting baselines activate areas associated with semantic relative to phonological tasks.…”
Section: Discussionsupporting
confidence: 90%
“…For example, baselines that require subjects to say "OK" to meaningless visual stimuli may increase demands on working memory and executive task processes while decreasing attention to perceptual processing. Likewise, there may be unpredicted processing that occurs during low-level baselines more than that during high-level baselines [Binder et al, 1999]. Our comparison of high-and low-level baselines might then reveal activation in unexpected regions.…”
Section: Introductionmentioning
confidence: 94%
“…Unfortunately, in fMRI aberrant activation patterns can result from subtraction. These areas of unusual activation may reflect "spontaneous neuronal activity", that is, areas not predicted by task demands, which cannot be experimentally controlled (Binder et al, 1999). A mismatch task is not cognitively demanding, in fact it is arguably pre-attentive (Naatanen 1990), possibly allowing for more "task-unrelated thoughts" (Binder et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These areas of unusual activation may reflect "spontaneous neuronal activity", that is, areas not predicted by task demands, which cannot be experimentally controlled (Binder et al, 1999). A mismatch task is not cognitively demanding, in fact it is arguably pre-attentive (Naatanen 1990), possibly allowing for more "task-unrelated thoughts" (Binder et al, 1999). These "task-unrelated thoughts" can result in changes in blood flow detected by BOLD method (Binder et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation